EARLY DIAGNOSIS OF CLIMATE IN PRIMARY HEALTH CARE - Eduarda Almeida de Souza, Cicera; Aparecido Nascimento Silva, Raylton; José Antônio da Silva, Fábio; Porto Valentim, Nayara; Torres de Almeida, Caroline; Ivonilda Sattler Maia Silva, Ingrid; Carlos Triches, Jean; Paula Moura Manzini, Ana; Xavier Arruda Costa, Yasmim; Yasmin Gomes de Lima, Ana (Health and Society, 2022)
Introduction: Women’s health has a history marked by a long process of building the SUS. The Comprehensive Assistance Program for Women’s Health (PAISM) was a public policy implemented with the aim of incorporating services for the promotion, prevention, assistance and recovery of women’s health throughout Brazil. In this perspective, the discussion about the different phases of a woman’s life that are still neglected by the services is inserted, such as the climacteric, when related to the symptoms, this phase is usually accompanied by many physical and emotional changes. Objective: To identify the importance of early diagnosis of climacteric in PHC, as well as treatment measures to minimize the symptoms of this period. Method: An integrative literature review was used, with a descriptive and exploratory approach, carried out in the following databases: SCIELO, BDENF, BRISA and LILACS. Results and Discussions: It was observed from the analysis of the literature, that during the climacteric phase, women go through many symptoms that cause discomfort to their well-being, in this way, it was evidenced that Primary Health Care has a essential role aimed at assisting these women, which involves the implementation of practices aimed at the early diagnosis and treatment of climacteric symptoms, of these, the consultations carried out by the PHC multidisciplinary team, is a starting point for women’s health care , reaching the PNAISM proposal. Final Considerations: Early diagnosis and guidance provided by the multidisciplinary team are of paramount importance for the promotion of women’s well-being. On the other hand, it is still evident that many professionals are not prepared to offer the proper care to them. Therefore, a training plan for continuing education is suggested for the professionals who make up the primary care services, especially the UBS.